Il concetto di controtransfert nella psicoanalisi da S. Freud a H. Racker - Grossi, Emanuela; Forte, Alberto (Il sogno della farfalla, 2014)
The article examines the evolution of the concept of countertransference in the first fifty years of its existence. The term was coined by Freud in 1910 as a reaction to the erotic countertransference of some analysts and to the therapeutic ambition demonstrated by others. According to what the authors define “the classical drive model”, the therapist had to remain neutral in the relationship with the patients and his emotional involvement was seen as a technical error. Even if the condemnation of countertransference was already challenged by S. Ferenczi in the 20s (who introduced the concept of empathy), it is only in the 50s that the concept is further expanded. P. Heimann and H. Racker formulated theories on countertrasference that view the emotional and ideational reaction of the therapist to the transference of the patient not only as an obstacle but also as an indispensable instrument for understanding. The article summarises Racker’s main affirmations in relation to this and ends with a reference to D. Winnicott’s works on countertransference in the therapy of psychotic patients.